Does the musical tempo enhance physical performance? - Aburto Corona, Jorge Alberto (2020)
The purpose of this study was to determine the effect of the musical tempo on heart rate (HR), rating of perceived exertion (RPE), and distance run (DR) during a treadmill aerobic test in young male and female adults. Participants ran on the treadmill listening to music at 140 beats per minute (bpm; M140), 120 bpm (M120), or without music (NM). No significant sex differences were found on HR (M140 = 172.6 ± 12.7, M120 = 171.9 ± 11.1, NM = 170.1 ± 12.2 bpm, p = .312), RPE (M140 = 7.5 ± 1.4, M120 = 7.6 ± 1.3, NM = 7.6 ± 1.2, p = .931), or DR (M140 = 4,791.4 ± 2,681.1, M120 = 4,900.0 ± 2,916.9, NM = 4,356.1 ± 2,571.2 m, p = .715). Differences were found in the effect of tempo on HR between condition M140 and NM (172.6 ± 12.7 vs. 170.1 ± 12.2 bpm, p = .044, η2 = 0.32). In conclusion, musical tempo does not affect performance, physiological, or perceptual variables in young adults exercising on a treadmill at a constant speed.